2006
DOI: 10.1021/ma060085+
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Light Scattering and Synchrotron Radiation Wide-Angle X-ray Diffraction Studies on Smectic Liquid Crystal Formation of Main-Chain Polyester

Abstract: Recent works on polymer crystallization have given considerable attention to the possibility that the crystal phase in the final semicrystalline state could be preceded by transient liquid crystal phases. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] At this aspect, it is interesting to investigate the smectic liquid crystallization process of polymer in which the developments of positional order as well as the orientational one are required. However, the liquid crystallization from the isotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
33
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(44 citation statements)
references
References 19 publications
11
33
0
Order By: Relevance
“…One-dimensional simulations were performed showing that the inclusion of the thermal energy balance corrects the standard Landau-de Gennes predictions of volume-driven growth under shallow quench conditions (5a-b) to experimentally observed [33,34] diffusion-limited growth. Additionally, the effect of incorporating thermal effects in the presence of meta-stable nematic pre-ordering was found to result in non-monotonic acceleration/deceleration/acceleration growth dynamics (6a-b), as observed experimentally [37]. This work sets the basis for further study of non-isothermal effects of the direct isotropic/smectic-A transition where an extended subset of liquid crystal physics present in the transformation is included (1).…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…One-dimensional simulations were performed showing that the inclusion of the thermal energy balance corrects the standard Landau-de Gennes predictions of volume-driven growth under shallow quench conditions (5a-b) to experimentally observed [33,34] diffusion-limited growth. Additionally, the effect of incorporating thermal effects in the presence of meta-stable nematic pre-ordering was found to result in non-monotonic acceleration/deceleration/acceleration growth dynamics (6a-b), as observed experimentally [37]. This work sets the basis for further study of non-isothermal effects of the direct isotropic/smectic-A transition where an extended subset of liquid crystal physics present in the transformation is included (1).…”
Section: Resultsmentioning
confidence: 57%
“…This has been experimentally observed in a smectic polymer liquid crystal which exhibits extremely slow dynamics [37]. The presence of a transient meta-stable nematic phase preceding the stable smectic phase in this polymer liquid crystal was observed under certain quench conditions [38].…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…The thermotropic phase behavior of a liquid-crystalline poly(ether ester) derived from 4 0 -hydroxybiphenyl-4-carboxylic acid and two different spacer diols (2-methyl-1,3-propanediol and R-1,3-butanediol) has been analyzed by differential scanning calorimetry, real time synchrotron X-ray diffraction and solid-state 13 C NMR. It has been found that the polymer develops a smectic mesophase that presents order inside the layers.…”
Section: Full Papermentioning
confidence: 99%